A Study of Women’s Glass Ceiling Beliefs and Turnover Intentions in Relation with OSE - Samar Masood; Dr. Samina Nawab; Dr. Khurram Shafi (Journal of Management Practices, Humanities and Social Sciences, 2021)
The main aim of the following quantitative study is to analyze the theoretical framework based on explanatory style by analyzing the association between women's beliefs related to the glass ceiling and turnover intentions and to determine whether occupational self-efficacy (OSE) moderated the connection of women beliefs regarding glass ceiling and their turnover intentions. Self-administered questionnaires were distributed, and online surveys were conducted from females that work in the private and public service sectors. The sampling technique that is used to conduct a survey from a female population is the purposive sampling technique. Women's beliefs related to the glass ceiling were analyzed using the career pathways survey (CPS), and turnover intentions were measured through the turnover intention scale. Analysis has been conducted by establishing the reliability and validity of the questionnaire scale and descriptive statistics, correlation technique, and multiple regression analysis to test the hypothesis. The findings and results indicated that there is a significant relationship among the main constructs. The findings also proved that occupational self-efficacy had a significant moderating effect on the optimistic and pessimistic (acceptance, resignation) beliefs and turnover intentions. These findings will be helpful for women to comprehend how their beliefs related to the glass ceiling works and how their beliefs influence the level of self-efficacy and intention to quit. The organization may further incorporate this study in order to devise prevention strategies to retain female employees in the workplace. It is one of the first studies to be conducted related to the glass ceiling beliefs in the Pakistani context.